2019
DOI: 10.1088/1742-6596/1246/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

EEG changes in patients with intracranial tumors and seizures symptom at Mohammad Hoesin Hospital Palembang

Abstract: This study was conducted to determine the EEG changes in intracranial tumor patients with symptoms of seizures and the correspondence between the location of tumor by the location of the EEG abnormality. This is a cross-sectional descriptive study using primary and secondary data. Samples were collected consecutively over a period of 1 year. Of the 35 samples, abnormal EEG in patients with primary intracranial tumors obtained 68,2%, whereas in metastatic intracranial tumors obtained in 84,6%. From the abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It has been reported that resting state EEG coherence is reduced in AD patients compared to cognitively healthy but depressed patients [ 106 ]. Furthermore, EEG coherence in AD subjects showed statistically significant differences compared to healthy controls [ 107 , 108 , 109 , 110 , 111 , 112 , 113 ]. Curiously, Sankari et al [ 108 ] found a significant decrease in EEG coherence in the delta band measured in temporal regions compared to healthy controls.…”
Section: Eeg Anomalies In Admentioning
confidence: 99%
“…It has been reported that resting state EEG coherence is reduced in AD patients compared to cognitively healthy but depressed patients [ 106 ]. Furthermore, EEG coherence in AD subjects showed statistically significant differences compared to healthy controls [ 107 , 108 , 109 , 110 , 111 , 112 , 113 ]. Curiously, Sankari et al [ 108 ] found a significant decrease in EEG coherence in the delta band measured in temporal regions compared to healthy controls.…”
Section: Eeg Anomalies In Admentioning
confidence: 99%
“…However, slowing annotation is critical as an abnormal amount of slowing in EEG suggests a neurological disorder, and an appropriate and timely treatment must be prescribed [162]. For instance, a localized and continuous EEG slowing may be associated with brain tumours [320]. Hence, identifying the brain region that exhibits pathological slowing help confirm and localize brain tumours [321].…”
Section: Introductionmentioning
confidence: 99%